2022
DOI: 10.3390/curroncol30010039
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity and Mortality after Surgery for Retroperitoneal Sarcoma

Abstract: Retroperitoneal sarcoma (RPS) is a rare disease with over 100 histologic types and accounts for 10–15% of all soft tissue sarcomas. Due to the rarity of RPS, sarcoma centers in Europe and North America have created the Transatlantic RPS Working Group (TARPSWG) to study this disease and establish best practices for its management. Current guidelines dictate complete resection of all macro and microscopic disease as the gold standard for patients with RPS. Complete extirpation often requires a multi-visceral res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…For the evaluation of patient candidacy for surgery in general, common perioperative evaluation includes baseline functional status, comorbidities, and nutritional status. Multiple studies have demonstrated a correlation between adequate perioperative nutrition and decreased complications [ 66 , 67 ]. Multiple indices exist that can be utilized in patient selection, including frailty and fragility indices, NISQIP, ASA, and Cardiac Risk calculators [ 68 , 69 , 70 , 71 , 72 ].…”
Section: The “Carefully Selected Patient”mentioning
confidence: 99%
“…For the evaluation of patient candidacy for surgery in general, common perioperative evaluation includes baseline functional status, comorbidities, and nutritional status. Multiple studies have demonstrated a correlation between adequate perioperative nutrition and decreased complications [ 66 , 67 ]. Multiple indices exist that can be utilized in patient selection, including frailty and fragility indices, NISQIP, ASA, and Cardiac Risk calculators [ 68 , 69 , 70 , 71 , 72 ].…”
Section: The “Carefully Selected Patient”mentioning
confidence: 99%